1991
DOI: 10.1111/j.1476-5381.1991.tb12342.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for an important species difference in the mechanism of 8‐OH‐DPAT‐induced hypothermia

Abstract: 1 Parallel series of experiments were carried out in the rat and mouse in order to investigate the mechanism(s) underlying the hypothermia induced in rodents by the selective 5-HT1A receptor agonist, 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT).2 In the mouse, lesioning of central 5-hydroxytryptaminergic neurones (by use of the neurotoxin, 5,7-dihydroxytryptamine; 5,7-DHT) abolished the hypothermic response to 8-OH-DPAT, and depletion of brain 5-hydroxytryptamine (5-HT) levels (with the 5-HT synthesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(96 citation statements)
references
References 19 publications
7
87
2
Order By: Relevance
“…3c) 5-HT1A receptor function was further evaluated in awake animals by assessing the effect of 8-OH-DPAT on body temperature. Systemic administration of 8-OH-DPAT is known to elicit a sudden and profound hypothermia, an effect that in mice is thought to be mainly mediated by presynaptic 5-HT1A receptor activation (32,33). Although the hypothermic effect of a 0.5 mg͞kg dose of 8-OH-DPAT was comparable in both genotypes, the administration of a lower dose (0.16 mg͞kg) resulted in a less pronounced hypothermic effect in Ϫ͞Ϫ than in ϩ͞ϩ mice.…”
Section: Resultsmentioning
confidence: 79%
“…3c) 5-HT1A receptor function was further evaluated in awake animals by assessing the effect of 8-OH-DPAT on body temperature. Systemic administration of 8-OH-DPAT is known to elicit a sudden and profound hypothermia, an effect that in mice is thought to be mainly mediated by presynaptic 5-HT1A receptor activation (32,33). Although the hypothermic effect of a 0.5 mg͞kg dose of 8-OH-DPAT was comparable in both genotypes, the administration of a lower dose (0.16 mg͞kg) resulted in a less pronounced hypothermic effect in Ϫ͞Ϫ than in ϩ͞ϩ mice.…”
Section: Resultsmentioning
confidence: 79%
“…Goodwin et al (1985aGoodwin et al ( , 1987a showed attenuation of the response in rats and mice both after PCPA and after injection of the serotonergic neurotoxin 5,7-dihydroxytryptamine (5,7-DHT), suggesting a presynaptic location, but it is noteworthy that the attenuation in rats was only seen when measured 14 days after the first PCPA injection and not when measured at 4 days post-PCPA. Evidence for a species difference was provided by Bill et al (1991), who showed that the response in rats was unaffected by 5,7-DHT and PCPA while that in mice was abolished. Although Hillegaart (1991) obtained a decrease in temperature on direct injection of 8-OH-DPAT into the dorsal raphe in rats, the dose of 8-OH-DPAT used was high and diffusion to postsynaptic sites may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Mianserin, which has equal affinity for the 5-HT 2A and 5-HT 2C receptor, and ketanserin, which is 100-fold selective for the 5-HT 2A versus 5-HT 2C receptor, also have high nanomolar affinity for alpha-adrenergic receptors (Leysen et al 1981). Although drugs interacting acutely with alpha-adrenergic receptors or dopaminergic receptors modulate 8-OH-DPAT-induced hypothermia in mice (Bill et al 1991;Durcan et al 1991), this has been shown not to be the case for 8-OH-DPAT-induced hypothermia in rats (Millan et al 1997). However, if mianserin or ketanserin treatment had modified 8-OH-DPATinduced hypothermia or forepaw treading in the current study, it would have been necessary to address the potential involvement of alpha-adrenergic receptors or 5-HT 2C receptors by investigating the effect of chronic administration of the alpha-1 antagonist prazosin or the selective 5-HT 2C receptor antagonist SB 206553 (Kennett et al 1996) on these 5-HT 1A receptor mediated behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacology of this response has been well characterized, demonstrating that 8-OH-DPAT-induced hypothermia is mediated by activation of 5-HT 1A receptors (Millan et al 1997;Scott et al 1994;Thielen et al 1996). Although it has been suggested that 8-OH-DPAT-induced hypothermia in rats is mediated by presynaptic receptors (Goodwin et al 1987b), the majority of evidence supports the view that in rats, the hypothermic response elicited by 5-HT 1A receptor agonists is mediated by postsynaptic receptors (Bill et al 1991;O'Connell et al 1992;Millan et al 1997 and discussion therein). 5-HT 1A receptor-mediated hypothermia has been used to assess the sensitivity of 5-HT 1A receptors following a variety of antidepressant treatments (Goodwin et al 1987a;Hensler et al 1991), and has been proposed as a model to screen and identify novel 5-HT 1A receptor agonists and antagonists (Millan et al 1997).…”
mentioning
confidence: 97%
See 1 more Smart Citation